Respuesta :
Answer:
- 12b+9=12b+11
9=11
- 6y-8=2 (3y-4)
6y-8=6y-8
- -3k+4=-2-6k
K=-2
Step-by-step explanation:
1.) Subtract 9 from both sides. (12b = 12b + 3)
Subtract 12b from both sides. (0 = 3)
This equation has no solutions, since we obviously know 0 cannot equal 3.
2.) Distribute the 2 on the right side. (6y - 8 = 6y - 8)
This equation has infinitely many solutions as both problems are exactly the same.
3.) Subtract 4 on both sides. (-3k = 2 - 6k)
Add 6k to both sides. (3k = 2)
Divide both sides by 3 to get k by itself. (k = 3/2)
Your answer for this equation is 3/2.
Hopefully this was helpful!
Subtract 12b from both sides. (0 = 3)
This equation has no solutions, since we obviously know 0 cannot equal 3.
2.) Distribute the 2 on the right side. (6y - 8 = 6y - 8)
This equation has infinitely many solutions as both problems are exactly the same.
3.) Subtract 4 on both sides. (-3k = 2 - 6k)
Add 6k to both sides. (3k = 2)
Divide both sides by 3 to get k by itself. (k = 3/2)
Your answer for this equation is 3/2.
Hopefully this was helpful!